Pengaruh Komitmen Profesional Dan Sosialisasi Antisipatif Mahasiswa Akuntansi Terhadap Niat Whistleblowing Dengan Religiusitas Sebagai Variabel Moderasi - Isfan Fajar Satrya; Herlina Helmy; Salma Taqwa (Jurnal Eksplorasi Akuntansi, 2019)
The accounting profession has emphasized the need for professionals to develop attitudes early in their careers, even before they moved professions. This study discusses the professional commitment and anticipatory socialization of accounting students towards whistleblowing intentions. Religiosity as a moderating variable that moderates the relationship between professional commitment and anticipatory socialization of accounting students to whistleblowing intentions. The population in this study is accounting students in the city of Padang. The sample is based on the purposive stratified sampling method. The data used in this study are primary data. This study used a questionnaire instrument from 277 respondents. The method of analysis is done by using MRA (Moderated Regression Analysis). The results showed that professional commitment had a significant effect on whistleblowing, but anticipatory socialization had a significant negative effect on whistleblowing. Religiosity weakens the relationship between professional commitment to whistleblowing but supports the relationship between anticipatory socialization of whistleblowing.